KEKOMUTATIFAN PADA GRUP PERMUTASI - Newton . (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Some research about cycle permutations and disjoints on cycle nonemptysets has been posted in some papers. However, the degree of the generalization of thisresult is varies. In this paper we studied the notion disjoint to be applied in arbitrarycollections of permutations on arbitrary nonempty sets.